Family communication and patient distress after germline genetic testing in individuals with pancreatic ductal adenocarcinoma. Issue 14 (12th April 2019) - Peters, Mary Linton B.; Stobie, Lindsey; Dudley, Beth; Karloski, Eve; Allen, Kyle; Speare, Virginia; Dolinsky, Jill S.; Tian, Yuan; DeLeonardis, Kim; Krejdovsky, Jill; Button, Arlene; Lim, Cynthia; et al.
Abstract : Background: Germline genetic testing currently is recommended for patients with pancreatic ductal adenocarcinoma (PDAC). In the current study, the authors assessed how often results are communicated to first‐degree relatives within 3 months and the emotional impact of testing on patients. Methods: A total of 148 patients who were newly diagnosed with PDAC and who had undergone testing of 32 cancer susceptibility genes at 3 academic centers were selected; 71% participated. Subjects completed the Multidimensional Impact of Cancer Risk Assessment (MICRA) and a family communication survey. The results of both surveys were assessed at 3 months according to the genetic test result (positive, negative, or variant of unknown significance [VUS]) and whether a patient met criteria for genetic testing. Results: A total of 99 patients completed the MICRA survey and 104 completed the family communication survey. The average age of the patients was 67 years, 47% were female, 29% had stage III/IV (AJCC 8th edition) disease, and 42% met genetic testing criteria. Approximately 80% of patients told at least 1 first‐degree relative about their result. There was a trend toward greater disclosure among patients who tested positive (93% vs 77% for those with a VUS result [ P = .149] and 74% for those who tested negative [ P = .069]). Patients not meeting genetic testing criteria were less likely to disclose results (69% vs 93%; P = .003). MICRA scores did not differ by test result, age, stage of disease, or sex. Conclusions: The rate of result communication was high, although it was lower among patients who did not meet genetic testing criteria, those who tested negative, or those who had a VUS result. Testing‐associated distress was similar across patient groups, and was comparable to that reported by other patients with cancer. Improved communication for all patients is crucial given the prognosis of PDAC, which limits time for disclosure. Abstract : In this prospective cohort study, the authors survey patients about their genetic testing experience using the Multidimensional Impact of Cancer Risk Assessment survey, a standardized instrument with which to measure distress, and ask about their disclosure of genetic testing results to first‐degree relatives. Positive test results do not appear to lead to significantly more distress, and a large percentage of patients are found to disclose test results to family members within 3 months.